The Role of School Principals in Increasing Student Interaction with Educational Platform in Light of Corona Pandemic from the point of view of teachers in the schools of Ajloun Governorate - Abu Hlail, Tawaseef Mousa Mustafa (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the role of school principals in increasing student interaction with educational platform in light of corona pandemic from teachers’ perspectives, the study used the descriptive analysis approach, a questionnaire was development consisted from (31) paragraph, the sample of study consisted from (650) male and female teachers. However, the findings of study showed that the role of school principals in increasing student interaction with educational platform in light of Corona pandemic from the teachers’ point of view came to a medium degree and with an arithmetic mean (3.66), and the arithmetic averages ranged between (1.75-4.60), and there weren’t any significant differences in the degree in the role of school principals in increasing student interaction with educational platform in light of Corona pandemic from teachers’ perspectives refer to variable of teacher’s sex (male| female). Furthermore, there were significant differences at (α ≤ 0.05) according to teacher qualification for higher education. Therefore, a set of recommendations was set one of the most importance was the necessity of holding training courses for school principals on the concept of educational platforms and benefit from them.